Job satisfaction and burnout of psychiatric nurses during the COVID-19 pandemic in China—the moderation of family support - Jin, Rui (Frontiers in Psychology, 2022)
Purpose The study aimed at investigating the state of psychiatric nurses’ job satisfaction, job burnout, and the moderating effect of family support between them in China during the COVID-19 pandemic. Materials and methods Online self-report questionnaires were distributed and 212 psychiatric nurses participated in the research. Pearson correlation analysis, multiple stepwise regression analysis, and simple slope test were used for data analysis. Results The results showed that the status of their job satisfaction (53.67 ± 10.72) and burnout (33.62 ± 13.84) did not reach a satisfactory level and job satisfaction had a significant negative impact on job burnout. Meanwhile, family support played a negative moderating role between the two variables. Conclusion Psychiatric nurses suffered from job burnout in China during the COVID-19. Family support could have a counterproductive effect when the nurses were experiencing decreasing job satisfaction. It gave suggestions to the medical institutions and the government to improve the psychological well-being of the psychiatric nurses and even of all the medical staff.